Civilizing Deficient Subjects: The New Rural Development Program and Trajectories of Rural Life in Late Socialist Vietnam - Hoàng, Cầm (Journal of Political Sociology, 2025)
Since 2010, the Vietnamese government has administered the New Rural Development Program to improve the quality of rural people’s lives. The program includes a set of 19 criteria for diagnosing problems, devising interventions and measuring changes. Villages must meet these criteria to be recognized as new rural communities. The criteria become not only a tool for authorities to govern rural people’s lives, but also a source of reference and meaning for rural people to change their conduct and navigate their futures. In the process of rectifying their perceived deficiencies and constructing new identities, rural people may complain about the excessive demands of the criteria, but still they look for ways to be recognized by the program rather than challenge its core ideas.